A single-extraction method using silver-thiourea for measuring exchangeable cations and effective CEC in soils with variable charges - Pleysier, J.L.; Juo, A.S.R. (1980)
The use of a single extraction with dilute unbuffered silver-thiourea (AgTU) solution (0.01 M Ag+) for measuring exchangeable cations and the cation exchange capacity (CEC) of soils was compared with the conventional effective CEC method, which used N NH4OAc displacement for exchangeable “bases” (Ca, Mg, K, Na) and N KCI extraction for exchange acidity (Al + H). Fifty-seven selected surface and lower B horizon samples of Alfisols, Ultisols, and Oxisols with low-activity clays derived from a wide range of parent materials were used. The two extraction methods gave essentially the same CEC values for all soils studied (R2 = 0.92). Good agreements were also obtained between the dilute AgTU-extractable bases (Ca, Mg, K, Na) and N NH4OAc-extractable bases. The dilute AgTU extraction gave slightly larger values of exchange acidity (Al + H) than the N KCl extraction for most soils. The single-extraction method using unbuffered Ag-thiourea is suitable for rapid, routine measurements of effective CEC and exchangeable cations for soils dominating in variable-charge colloids.